Complete genome sequence analysis of two human enterovirus C99 strains isolated in Xinjiang Uighur Autonomous Region, China, in 2011 - Sun, Qiang; Zhang, Yong; Cui, Hui; Zhu, Shuangli; Li, Xiaolei; Huang, Guohong; Tang, Haishu; Yan, Dongmei; Wang, Dongyan; Xu, Wenbo (Archives of virology, 2014)
Human enterovirus C99 (EV-C99) is a new member of the species Enterovirus C, and although only a few EV-C99 sequences have been obtained thus far, the strain has been identified on four continents. In 2011, two EV-C99 strains were isolated from two healthy children in Xinjiang, China, and to our knowledge, this is the first finding of EV-C99 in China. The two strains, designated HT-XEBGH09F and KSSC-ALXHH01F, showed 78.8–86.6 % similarity to other EV-C99 strains and exhibited intra-serotypic genetic recombination within the P2 coding regions. These findings reflect high genetic divergence among the EV-C99 strains.